2015
DOI: 10.1103/physreva.91.042302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum annealing correction for random Ising problems

Abstract: We demonstrate that the performance of a quantum annealer on hard random Ising optimization problems can be substantially improved using quantum annealing correction (QAC). Our error correction strategy is tailored to the D-Wave Two device. We find that QAC provides a statistically significant enhancement in the performance of the device over a classical repetition code, improving as a function of problem size as well as hardness. Moreover, QAC provides a mechanism for overcoming the precision limit of the dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 53 publications
4
121
0
Order By: Relevance
“…In order to quantify the performance of the QAC scheme, we also test two classical strategies and one additional quantum strategy [40][41][42].…”
Section: Benchmarking Using Antiferromagnetic Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantify the performance of the QAC scheme, we also test two classical strategies and one additional quantum strategy [40][41][42].…”
Section: Benchmarking Using Antiferromagnetic Chainsmentioning
confidence: 99%
“…Work on the first generation D-Wave 1 (DW1) "Rainier" and second generation D-Wave 2 (DW2) "Vesuvius" processors has already demonstrated that error correction can substantially benefit quantum annealing [40][41][42]. Namely, it was shown that even a relatively simple quantum repetition code incorporating energy penalty terms and a decoding procedure, can significantly improve the success probability of finding ground states, as well as overcome precision issues in the specification of the Ising Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…For such flux qubits, the T 2 time can at present range from tens of nanoseconds to a few hundred nanoseconds [21,22], yet the computation lasts on the order of microseconds to milliseconds. If the qubits have all decohered long before the computation is over, how can this be reconciled with evidence that the D-Wave devices perform quantum annealing [23][24][25][26][27][28][29][30][31][32]? In essence, the answer boils down to two key points:…”
Section: Introductionmentioning
confidence: 99%
“…This scaling is not an inherent part of the quantum isomer search algorithm. Increasing the problem size decreases the probability of finding a successful answer due to annealing error and imperfect hardware [48]. It is not surprising that more runs are needed for larger molecules, especially when the quadratic scaling of parameters and the limited connectivity of the D-Wave 2000Q's chimera graph are taken into account.…”
Section: Discussionmentioning
confidence: 99%